Endoscopic Ultrasound-guided Biliary Drainage: A Tailored Approach - Majid Abdulrahman Almadi; Motib H AlAbdulwahhab (Wolters Kluwer Medknow Publications, 2018)
Although endoscopic retrograde cholangiopancreatography (ERCP) remains the gold standard method to achieve biliary drainage (BD) in cases of obstruction, some situations preclude this option. Alternatively, percutaneous BD is associated with a number of limitations and more recently associated risks have been found to be higher than those with nonconventional interventions such as endoscopic ultrasound-guided BD (EUS-BD). EUS-BD encompasses a number of interventions and approaches depending on the underlying cause and position of obstruction. We present a case series of six cases where EUS-BD was used when ERCP was not possible or failed at a tertiary care academic center. We also describe the different types of EUS-BD based on the nomenclature that has been proposed by the Asian EUS group (AEG). In all the cases that were presented, EUS-BD was successful with no complications or adverse events. The intervention resulted in resolution of biliary obstruction and the patients underwent the planned treatment for their underlying disease. In this case series, we introduced the concept of EUS-BD to the nonspecialist and illustrated the variability of the procedure and its agile nature when applied in the right setting and with the proper expertise and the importance of the presence a complete team approach by different specialists when caring for these patients.